Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
7
Step-by-step explanation:
Given,
h ( x ) = 1
To find : -
h ( x ) = 3x + 4
h ( 1 ) = 3 ( 1 ) + 4
= 3 + 4
h ( 1 ) = 7
Step-by-step explanation:
h(x) = 3x + 4
h(1) = 3(1) + 4
h(1) = 3 + 4
h(1) = 7 ans.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.